Powerpoint as a Useful Tool in Corrective Osteotomies Calculation—Case Report and Presentation of the Method - Pérez, Daniela; Martins, Mariana da Rocha Sousa Camello; del Valle, Montserrat; Ferreres, Ángel (Revista Iberoamericana de Cirugía de la Mano, 2019)
Malunion or congenital disorders of the forearm might lead to biomechanical alterations and change the pronosupination motion. Occasionally, an osteotomy should be performed to correct this malalignment. Several techniques have been reported, especially 3D modeling, which is not yet widely used due to its cost. The traditional method is still mostly performed, but sometimes it may be difficult to do the preplanning. In this paper, we explain an easy method, called “giro point” technique, to perform the calculation of osteotomies using commercially available software. We present six clinical cases with good functional results, in which the calculation was performed using this method. The method is easy to follow, with adequate surgical-radiological correlation.
Keywords: osteotomy; PowerPoint; pronosupination; malalignment